Alexander the Great - Beddall, Fiona (Chicago : Childrens Press, 2008)
Traces the life of the warrior king of Macedonia who conquered and united the known world of his time.
Booklist.
School Library Journal.
Level 4.
Keywords: Alexander, -- the Great, -- 356-323 B.C. -- Juvenile literature; Alexander, -- the Great, -- 356-323 B.C.; Alexander, -- the Great, -- 356-323 B.C.; Generals -- Greece -- Biography -- Juvenile literature; Generals; Kings, queens, rulers, etc; Generals -- Biography; Kings, queens, rulers, etc. -- Biography; Greece -- History -- Macedonian Expansion, 359-323 B.C. -- Juvenile literature; Greece -- Kings and rulers -- Biography -- Juvenile literature; Greece -- History -- Macedonian Expansion, 359-323 B.C.; Greece -- History